Measurement Properties of the Oswestry Disability Index in Recipients of Lumbar Spine Surgery. Issue 2 (15th January 2021) - Cook, Chad E.; Garcia, Alessandra N.; Wright, Alexis; Shaffrey, Christopher; Gottfried, Oren
Abstract : Study Design: This is an observational study on the measurement properties of the Oswestry Disability Index (ODI) version 1.0. Objectives: To (1) determine the construct validity of the tool, specifically structural validity; (2) analyze the criterion validity of the tool, specifically concurrent validity against proxy measures of pain, function, and quality of life and predictive validity of each item to proxy measures of disability; and (3) reliability of the tool, specifically internal consistency. Summary of Background Data: We endeavored to investigate the measurement properties of the ODI on a spine surgery population to test the assumption that a more disabled population may influence the properties of the tool. Methods: Data were pulled from the Quality Outcomes Database (QOD) Spine Registry. A total of 57, 199 participants who underwent primary or revision lumbar spine surgeries were included. Structural validity was assessed by exploratory and confirmatory factor analysis, concurrent validity, predictive validity by odds ratios, and internal consistency by Cronbach alpha. The Visual Analog Scale for back pain, two standard open questions, and the EuroQol 5 Dimension/Visual Analogue Scale were included as proxy measures of pain, function, and quality of life, respectively. Hospital readmission, return to operating room for treatment and revision surgery (all within 30 days) were included as proxy measures of disability to assess the predictive validity of each ODI item. Results: The ODI demonstrated a two-factor structural solution, which explained 54.9% of the total variance. Fair internal consistency (0.74–0.77), and fair criterion validity (concurrent) and significant findings with predictive validity ( P  < 0.01) substantiated the use of each item of the ODI as well as the summary score and ODI thresholds. Conclusions: Our study lends value to a burgeoning repository of evidence that suggests the ODI is a useful tool for capturing outcomes in clinical practice. We recommend its continued use in clinical practice. Level of Evidence: 4 Abstract : This study examined the structural validity, the concurrent validity, predictive validity and the internal consistency of the ODI Version 1.0. Data of 57, 199 individuals who received spine surgery were pulled from a large spine surgery repository. The ODI demonstrated good measurement properties in a population of individuals who receive spine surgery